Difference in the Prevalence of Elevated Blood Pressure and Hypertension by References in Korean Children and Adolescents - Kim, Jeong Yeon; Cho, Heeyeon; Kim, Jae Hyun (Frontiers in Medicine, 2022)
The prevalence of pediatric hypertension and obesity has increased over the past decades. Pediatric hypertension and obesity are associated with adult hypertension, metabolic syndrome, and cardiovascular disease. There are two main pediatric blood pressure (BP) classification guidelines, the “Clinical Practice Guideline for Screening and Management of High Blood Pressure in Children and Adolescents” (AAP 2017) and “2016 European Society of Hypertension guidelines for the management of high BP in children and adolescents” (ESH 2016). No study has classified Korean youths with cardiometabolic risk. This study analyzed the prevalence of high BP according to AAP 2017 (elevated BP and hypertension) and ESH 2016 (prehypertension and hypertension) in Korean children. Additionally, the cardiometabolic risk factors (CMRFs) were compared between children who were hypertensive in AAP 2017 but normotensive in ESH 2016 (upward reclassified) to those who were normotensive in both AAP 2017 and ESH 2016. Data were extracted from the Korea National Health and Nutrition Examination Survey, 2016–2018. A total of 1,858 children aged 10-17 years were included in the analysis. The prevalence of elevated BP/prehypertension and hypertension was 4.1% and 6.5% by ESH 2016, and 8.9% and 9.4% by AAP 2017 in Korean youth, respectively. The AAP 2017 reclassified 11.9% of youth in the upper BP class. When those upward reclassified youth were compared to those who were normotensive in both AAP 2017 and ESH 2016, reclassified youth were male predominant (77.1% vs. 49.6%, p<0.001), older (14.6 vs. 13.8, p<0.001) and showed higher body mass index (BMI) z-score (0.77 vs. 0.15, p<0.001) and more overweight/obesity (14/30.6% vs. 13.3/6.4%, p<0.001) and severe CMRFs (triglyceride 83.32 mg/dL vs. 72.9 mg/dL, p=0.011; high-density lipoprotein cholesterol 47.3 mg/dL vs. 51.1 mg/dL, p<0.001; alanine transaminase 21.7 IU/L vs. 14.7 IU/L, p=0.001, uric acid 5.89 mg/dL vs. 5.22 mg/dL, p<0.001; metabolic syndrome 13.2% vs. 1%, p<0.001). In conclusion, AAP 2017 showed a higher prevalence of abnormal BP in Korean youth, and those upward reclassified by AAP 2017 were more obese and had severe CMRFs than normotensive Korean children. The AAP 2017 could allow the early detection of Korean youth with more CMRFs.